Dialektika Semantik Strukturalisme, Post Strukturalisme dan Teologi Injili - Papay, Alexander Djuang; Belay, Yosep (Sekolah Tinggi Teologi Intheos Surakarta, 2024)
Abstract. Meaning is correlated with actual actions, both in communication and ideology and social relations, so that the issue of meaning is now the focus of contemporary scientific study and criticism. The Christian faith, which specifically constructs a system of theology, worldview and ethics based on Biblical texts, is also faced with the challenge of interpreting the meaning of Biblical texts. From this struggle, this article discusses the issue of semantic theory from three perspectives, namely: structuralism, post-structuralism, and evangelical theology. Through this article, the author aimed to analyze semantic issues so that it is hoped that it will be able to present appropriate semantic constructions for approaches to Christian hermeneutics and theology in facing existing challenges. The method used was literature study. The results of this research showed that there are several similarities between the semantic theory of structuralism and Christian theology which is characterized by a constructive approach to meaning with several important notes. On the other hand, these two approaches are not in line with the semantic pattern of post-structuralism which is deconstructive, radical and tends to be agnostic.Abstrak. Makna terkorelasi dengan tindakan aktual, baik dalam komunikasi maupun ideologi dan relasi sosial, sehingga persoalan makna kini menjadi fokus kajian dan kritik keilmuan kontemporer. Iman Kristen yang secara khusus mengonstruksikan sistem teologi, wawasan dunia hingga etika yang berbasis pada teks-teks Alkitab, juga diperhadapkan dengan tantangan persoalan pemaknaan teks-teks Kitab Suci. Dari pergumulan tersebut, artikel ini membahas mengenai persoalan teori semantik dalam tiga perspektif yaitu: strukturalisme, post strukturalisme, dan teologi Injili. Melalui artikel ini penulis hendak mengurai persoalan semantik sehingga diharapkan mampu menghadirkan konstruksi semantik yang tepat bagi pendekatan hermeneutika dan teologi Kristen dalam menghadapi tantangan yang ada. Metode yang digunakan adalah studi literatur. Hasil penelitian ini menunjukkan bahwa terdapat beberapa kesamaan antara teori semantik strukturalisme dengan teologi Kristen yang bercirikan pendekatan makna konstruktif dengan beberapa catatan penting. Sebaliknya, kedua pendekatan tersebut tidak sejalan dengan pola semantik post strukturalisme yang dekonstruktif, radikal dan cenderung agnostik.